2017
DOI: 10.1186/s12978-017-0333-2
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive practices among married women of reproductive age in Bangladesh: a review of the evidence

Abstract: BackgroundBangladesh has experienced a sevenfold increase in its contraceptive prevalence rate (CPR) in less than forty years from 8% in 1975 to 62% in 2014. However, despite this progress, almost one-third of pregnancies are still unintended which may be attributed to unmet need for family planning and discontinuation and switching of methods after initiation of their use.MethodsWe conducted an extensive literature review on contraceptive use among married women of reproductive age (MWRA) in Bangladesh. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 9 publications
9
59
4
Order By: Relevance
“…A 2006 study on OCP discontinuation in rural Bangladesh found that women who had consulted a trained worker prior to getting on the pill had a minimum use period of twelve months while women who did not have proper counselling from a trained worker had a minimum use time of one month [5]. A more recent study aimed at identifying the practices that led to unintended pregnancies in Bangladesh, recommended after its ndings, to increase trained eld workers who can ensure distribution of OCP supplies and provide counselling and support for the families, through the family planning program [18].…”
Section: Discussionmentioning
confidence: 99%
“…A 2006 study on OCP discontinuation in rural Bangladesh found that women who had consulted a trained worker prior to getting on the pill had a minimum use period of twelve months while women who did not have proper counselling from a trained worker had a minimum use time of one month [5]. A more recent study aimed at identifying the practices that led to unintended pregnancies in Bangladesh, recommended after its ndings, to increase trained eld workers who can ensure distribution of OCP supplies and provide counselling and support for the families, through the family planning program [18].…”
Section: Discussionmentioning
confidence: 99%
“…• Low (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) • Moderate (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) • High (34-44) Fourthly, Perceived barriers: It included (11items) from 11-44 and it ranked as follow:…”
Section: Tools Of Data Collection: Two Tools Were Used For Data Collementioning
confidence: 99%
“…Many studies indicate that the main reason for the high growth rate of the population is the low use of contraceptives, especially in rural areas where the vast majority of the country's population lives. 1,2 This low contraceptive prevalence rate (CPR) may be attributed to son preference as well as to a wide variety of social, economic, cultural, and demographic factors. Moreover, the use of contraceptives is affected by gender composition and number of living children in the family.…”
Section: Introductionmentioning
confidence: 99%